Aspectos semióticos e lexicogramaticais de peças publicitárias: a construção de uma leitura multimodal - Zaira Bomfante dos Santos (2009)
In the national academic context there is an increasing interest inmultimodal studies due to many transformations in the semiotic visual communication landscape. These transformations have produced effects in the form and in the characteristics of the way of writing where many semiotic modes are used to elaborate texts, giving them specific meanings and interpretations in a given context. From thisperspective, the present work sets out to provide data for the study of multimodal texts by means of an analysis of advertisements of beauty and hygiene products taken from the feminine magazines "Nova" and "Marie Claire" in the period of July to December 2008, since they are examples of a precise articulation of many semiotic modes in theirconfiguration.The aim of this study is, mainly, to check the semiotic articulation modes in these texts and the meaning produced by them for a critical reading. This work will have as a theorical basis Social Semiotics, Systemic-Functional Grammar and the Multimodal Approach (HODGE, KRESS, 1988, KRESS e VAN LEEUWEN 2001, 2006, HALLIDAY and MATTHIESSEN, 2004). The methodology used for this work isbased upon system network related to representational, interactive and compositional meanings of the verbal and visual components. The results show that the choices made, from the verbal texts to the combination of images must be considered in the appreciation of the texts, which enclose complex meanings in the context where theybelong. The choices give a meaningful potential to the texts once they give evidence of what consumers engaged in a social practice of taking care of the body are searching: efficient products that promote not only care but also beauty.